ANALISIS PENGARUH PROMOSI, HARGA, DAN ATRIBUT PRODUK TERHADAP PERPINDAHAN MEREK (BRAND SWITCHING) KARTU SELULER DI STIE TOTALWIN SEMARANG - Jatmiko, M. Roby (Master of Management Diponegoro University, 2013)
Brand Switching is the time when a customer or a group of customerchange their loyalty from one brand of product to another.Population of this research is SIM Card User in Totalwin Semarang. Sixty eight are chosen as sample are fixed as purposive sampling. Data are analyzed using SPSS program. Data are collected with questionnaires.From the research we can conclude that validity test and reliability test all questioner are fulfill the requirement. Result and theoretical implication of this research is: this research supports previous researches postulating that promotion, price , and product attributes influences to brand switching positively. In managerial terms, this research contributes to decision makers to pay more attention to the promotion in purpose to improve loyalty customer.